Using Zoom to Support English Learning during Covid-19 Pandemic: Strengths and Challenges - Mu'awanah, Nafisatul; Sumardi, Sumardi; Suparno, Suparno (Jurnal Ilmiah Sekolah Dasar, 2021)
COVID-19 pandemic caused educational institutions apply remote distance learning policy. Zoom is one of popular platforms to optimize online learning through video conference. This study aimed to explore strengths and challenges of using Zoom to support distance English learning. A qualitative approach with narrative inquiry design was employed and students from a junior high school voluntarily participated. Interview was deployed as data collection methods, and the data were validated by triangulation and analyzed by following the interactive model analysis. The study reveals that learning English via Zoom help students to practice English, make teaching-learning process more effective, and facilitate the teacher-student interaction and communication. Moreover, features on Zoom support distance English learning. Those all benefits bring good impact on students’ English learning output. Meanwhile, Zoom is also challenging for students with slow internet connection and unsupported gadget. The activity also spends extra cost for internet bill and need conducive learning environment. It is suggested that government needs to provide better facilities to support online learning, such as providing good internet access.